Contact metamorphism - Kerrick, Derrill M. (Reviews in mineralogy, 2018)
Volume 26 of Reviews in Mineralogy provides a multidisciplinary review of our current knowledge of contact metamorphism. As in any field of endeavor, we are provided with new questions, thereby dictating future directions of study. Hopefully, this volume will provide inspiration and direction for future research on contact metamorphism.The Mineralogical Society of America sponsored the short course on Contact Metamorphism, October 17-19, 1991, at the Pala Mesa Resort, Fallbrook, California, prior to its annual meeting with the Geological Society of America.